2021
DOI: 10.5194/bg-18-467-2021
|View full text |Cite
|
Sign up to set email alerts
|

Extending a land-surface model with <i>Sphagnum</i> moss to simulate responses of a northern temperate bog to whole ecosystem warming and elevated CO<sub>2</sub>

Abstract: Abstract. Mosses need to be incorporated into Earth system models to better simulate peatland functional dynamics under the changing environment. Sphagnum mosses are strong determinants of nutrient, carbon, and water cycling in peatland ecosystems. However, most land-surface models do not include Sphagnum or other mosses as represented plant functional types (PFTs), thereby limiting predictive assessment of peatland responses to environmental change. In this study, we introduce a moss PFT into the land model c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 142 publications
0
24
0
Order By: Relevance
“…Lichens can contribute significantly to C uptake and N fixation in arctic ecosystems (Crittenden & Kershaw, 1978;Lange et al, 1998) and play important ecological roles including forming an essential part of the caribou diet in the winter (Longton, 1997). While some large-scale models have begun to integrate nonvascular PFTs and their particular traits (e.g., Druel et al, 2019;Shi et al, 2021), ELM has, until now, lacked specific capability for nonvascular arctic PFTs. In this study, bryophytes and lichens were implemented within the existing PFT framework as nonwoody plants with very low belowground biomass.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lichens can contribute significantly to C uptake and N fixation in arctic ecosystems (Crittenden & Kershaw, 1978;Lange et al, 1998) and play important ecological roles including forming an essential part of the caribou diet in the winter (Longton, 1997). While some large-scale models have begun to integrate nonvascular PFTs and their particular traits (e.g., Druel et al, 2019;Shi et al, 2021), ELM has, until now, lacked specific capability for nonvascular arctic PFTs. In this study, bryophytes and lichens were implemented within the existing PFT framework as nonwoody plants with very low belowground biomass.…”
Section: Discussionmentioning
confidence: 99%
“…More model improvements are needed to accurately represent bryophyte and lichen physiology in ELM. To this end, Sphagnum physiological processes such as capillary wicking of water and coupling of photosynthetic rate to tissue water content are being developed in ELM for northern peatland ecosystems (Shi et al, 2021), and these developments could be incorporated into arctic bryophyte simulations in the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus the inclusion of a moss PFT and its unique functions in land surface models like JULES should be a priority, and indeed several models have done this (e.g. Porada et al (2016); Chaudhary et al (2017); Shi et al (2021)).…”
Section: Next Steps For Modelling Global Peatlands: Hydrology and Vegetationmentioning
confidence: 99%
“…In this study, we reported on the simulating effects of warming and eCO 2 on CH 4 cycling in a northern Minnesota peatland under various warming and eCO 2 scenarios by using the ELM-SPRUCE model, a version of ELM designed for this experiment (Ricciuto et al, 2021;Shi et al, 2015Shi et al, , 2021. As the second in a series of two modeling papers, we expanded upon the model description provided by Ricciuto et al (2021) and explored the warming and eCO 2 impacts on CH 4 cycling and further compared the simulated processes against observational data obtained from a global meta-analysis.…”
mentioning
confidence: 99%